Design and development of an integrated mixing and injection moulding machine for micro metal parts / Abdullahi Aliyu Alhaji - Abdullahi Aliyu , Alhaji (2017)
Development of a new powder injection moulding (PIM) feedstock or in-house processing require robust mini-lab mixer and moulding machine. Meanwhile, tooling design, part design and process design are identified as aspects of PIM technique that require continuous improvement through engineering design approach. Therefore, the aim of this study is to develop an integrated machine suitable for mixing powder-binder and injection moulding of PIM feedstock. Machine fabrication is carried out and optimised by simulation driven design. Performance testing of the machine was conducted and variability in mass of PIM green parts were examined. Furthermore, Taguchi method was adopted for the design of experiments and analysis. Empirical models for prediction of aluminium PIM feedstock viscosity is developed by response surface methodology. Homogeneity and determination of the best suitable backbone polymer for the wax-based aluminium PIM feedstock is investigated by thermal characterization. Density and rheological properties were used to determine the optimum solid loading of aluminium PIM feedstock. Aluminium PIM feedstock samples were moulded, debound and sintered under argon atmosphere. The quality of green and sintered aluminium PIM parts were evaluated based on physical and mechanical properties of the product at various processing stage of the PIM technique. Surface morphology, density and strength of aluminium PIM samples were investigated. In addition, the composition of the powder, green and sintered aluminium PIM samples were examined by energy dispersive x-ray (EDX). The optimum solid loading of aluminium PIM feedstock investigated was found to be 62 vol.% with mouldability index of 5.96 ×10-6 Pa −1K−1. Quality investigations show that aluminium PIM green density (2.02 gcm-3), strength (10.95 MPa) and sintered aluminium PIM samples were achieved with tensile strength of 10.17 MPa. A custom-made machine with capability of mixing and injection moulding of micropart is developed.